Mobile Map-Based Positioning System Using Segmentation Algorithm (MM-BPS) - Migdady, Hazem Moh'd Ali (2008)
The rapid deployment of mobile technology has increasingly provided people and organizations with ability to work away from office and be always on run. The mobile technology was developed to create ubiquitous environment where information can be access at any place and at any time. In the positioning process, the navigator needs to identify the position of his/her final destination in order to reduce any required efforts, and to make the right decision to choose the most suitable way. Knowing the locations is important in the navigation strategy. The major aim of this research is to provide the Navigators with information about his/her final destination according to his/her current location during the navigation. The research has targeted on UUM vital buildings. Vaishnavi and Kuechler Methodology has been implemented in various applications and it considered as a general methodology to develop totally new algorithms and create new information according to the accumulated information. This paper reports steps to build a segmentation positioning algorithm and to implement Mobile Map-Based Positioning System prototype.